Factors influencing the performance of government-linked investment companies in Malaysia / Nadhirah Farzana Rozman - Rozman, Nadhirah Farzana (Faculty of Business Management, 2018)
Government-Linked Investment Companies (GLIC) is considered as one of a powerful engine to promote economic growth in Malaysia which could lead to rapid expansion of globalization. Ministry of Finance has become the most powerful player in the Malaysian economy which greatly impacts the economy by its state intervention and politics according to Free Malaysia Today, (2018). It could stimulate the economy of the country as it is one of the biggest substances to development. The Performance of GLIC in Malaysia is still uncertain due to external and internal factors of the economy and the firm itself. This research is undertaken with an aim to measure and identify influences on the performance of Government-Linked Investment Companies in Malaysia. This study focused on using data collection method from respective firm's annual report which the period of data analysis covers from 2010-2016. In addition, this study will be using return on asset as the dependent variable and firm size, leverage, and liquidity as the independent variables as measurement for the performance of Government-Linked Investment Companies in Malaysia. There are five companies selected in this study which are Khazanah Nasional Berhad, Kumpulan Wang Simpanan Pekerja, Lembaga Tabung Haji, Lembaga Tabung Angkatan Tentera, and Kumpulan Wang Persaraan. Evidence found from the previous studies by other researcher stating that the firm size, leverage, and liquidity carry a negative impact. However, in this study all independent variables outcomes are significantly related to performance although it carries a negative impact. Moreover, this study will be using the panel least square statistical method to test for the independent and dependent variables relationship.